The genus Centorisoma Becker in China, with a key to world species (Diptera, Chloropidae) - Liu, Xiaoyan; Yang, Ding (Zootaxa, 2012)
A review of the species of the genus Centorisoma Becker from China is provided. The following 5 species are described as newto science: C. divisum sp. nov., C. gansuensis sp. nov., C. helanshanensis sp. nov., C. scutatum sp. nov. and C. shaanxiensis sp. nov. A key to the world species of genus Centorisoma is given.